Levantamiento geológico – estructural, escala 1:1 000 de la vía Loja – Saraguro, abscisas km 60+100 hasta km 64+900, Cantón Saraguro, Provincia de Loja - Pardo Cruz, Josselyn Gabriela (2023)
The Panamericana highway E-35, Troncal de la Sierra, Loja – Saraguro, connects Loja and Azuay provinces, which being a first-order road is used by transporters and pedestrians constantly, however, the road damage is important from the beginning of its construction, for this reason a specific study sector was delimited where greater road damage was observed, among the progressive ones, km 60+100 La Quesera sector to km 64+900 Las Lagunas sector, with 4.5 km of length and 200 m of strip, covering an area of 1.76 km2. Having as its main research objective to know the structural geological conditions of the sector, the topographic survey was based on the tachymetry method using the total station, then through the photointerpretation technique the geology and geological structures were interpreted, later this information was corroborated in the field, finally represented in a structural geological map using GIS tools, which reflects the geological and structural conditions of the study sector. In this way, the delimited sector presents a relief with medium slopes and medium to high hills, lithologically, volcanic materials of the ignimbritic tuff and lithic tuff type predominate corresponding to the Rio Sinincapa and Quebrada Tasqui units, having a metamorphic basement composed of phyllite belonging to the Chigüinda Unit. Keywords: lithology, fracturing, photointerpretation, morphology.